The Identification, Environmental Factors, and Fungicide Sensitivity of Colletotrichum siamense Causing Leaf Disease of Oil Palm (Elaeis guineensis) in China - Haipeng Li; Qiangqiang Pang; Zhuoying Wang; Changchang Jiang; Xiaodong Sun; Zhenghui Liu; Man Zhou; Yisong Chen; Qiang Bian (Agronomy, 2025)
This study aimed to identify the pathogen of oil palm (Elaeis guineensis) leaf spot disease in Hainan Province, China and examine the effects of environmental factors and fungicide sensitivity on the pathogen. The research confirmed that the pathogen responsible for this novel leaf spot disease was Colletotrichum siamense, marking the first report of this pathogen on oil palm in China. Field observations revealed summer-onset disease symptoms with concomitant leaf damage. The pathogen demonstrated optimal growth at a temperature of 30 °C and pH of 7.0, indicating its adaptability to prevailing climatic conditions in the region. Laboratory tests assessed the effects of various environmental factors on mycelial growth, revealing a marked decline in growth at temperatures below 20 °C and above 35 °C, as well as at acidic pH levels. Fungicide sensitivity assays identified pyraclostrobin, tebuconazole, prochloraz, and carbendazim as the most effective compounds, significantly inhibiting the growth of C. siamense with low EC50 values. These findings provide essential information for developing effective disease management strategies to combat leaf spot disease in oil palm plantations.